Knowledge on birth preparedness and complication readiness among expecting couples in rural Tanzania: Differences by sex cross-sectional study - Moshi, Fabiola V.; Ernest, Alex; Fabian, Flora; Kibusi, Stephen M. (PLOS ONE, 2018)
Background Inadequate knowledge of birth preparedness and complication readiness (BPCR) among expecting couples delays timely access to maternal emergency services. The aim of this study was to assess knowledge on birth preparedness and complication readiness and how men and women differ" among expecting couples in a rural setting of Rukwa Region, Tanzania. Methods A community-based cross-sectional study targeting pregnant women and their partners was performed from June 2017 to October 2017. A total of 546 couples were sampled using three-stage probability sampling techniques and then interviewed using a structured questionnaire. The mean score difference was sought using independent t-test. Multiple linear regressions were performed to determine the predictors of knowledge. Results There was a significant difference in mean knowledge scores between pregnant women (M = 5.58, SD = 4.591) and male partners (M = 4.37, SD = 4.285); t (1085) = -4.525; p<0.001. Among women, BPCR levels were positively influenced by age (β = 0.236; p<0.01), having ever heard about birth preparedness (β = 0.176;p<0.001), being of Mambwe ethnicity (β = 0.187; p<0.001), living near a health center rather than a dispensary (β = 0.101;p<0.05) and having had a prior preterm delivery (β = 0.086;p<0.05). Access to media through radio ownership negatively influenced BPCR levels among both women (β-.119; p<0.01) and men (β = -0.168; p<0.0001). Among men, the BPCR knowledge was only positively influenced by having ever heard about birth preparedness (β = 0.169;p<0.001), age at marriage (β = -0.103; p<0.05), and having completed either primary (β = 0.157;p<0.001) or secondary education (β = 0.131;p<0.01). Conclusion Some important predictors of knowledge were revealed among women and men, but overall knowledge about birth preparedness and complication readiness was low. This study demonstrates inadequate knowledge and understanding at the community level about key elements of birth preparedness and complication readiness. In order to improve access to life-saving care for women and neonates, there is a pressing need for innovative community strategies to increase knowledge about birth preparedness and complication readiness. Such strategies are essential in order to reduce maternal and neonatal mortality in rural Tanzania.